Motion control applications: observer based DC motor parameters estimation for novices - Branesh M Pillai; Jackrit Suthakorn (Institute of Advanced Engineering and Science, 2019)
Estimation of motor inertia and friction components is a complex and challenging task in motion control applications where small size DC motors (<100W) are used for precise control. It is essential to estimate the accurate friction components and motor inertia, because the parameters provided by the manufacturer are not always accurate. This research proposes a Sensorless method of determining DC motor parameters, including moment of inertia, torque coefficient and frictional components using the Disturbance Observer (DOB) as a torque sensor. The constant velocity motion test and a novel Reverse Motion Acceleration test were conducted to estimate frictional components and moment of inertia of the motor. The validity of the proposed novel method was verified by experimental results and compared with conventional acceleration and deceleration motion tests. Experiments have been carried out to show the effectiveness and viability of the estimated parameters using a Reaction Torque Observer (RTOB) based friction compensation method.